Keselamatan Maritim di Indonesia Akibat Pengaruh dari The International Convention for the Safety of Life at Sea (SOLAS 1974) - Anastasia Zefanya (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
A report from Research and Markets estimates that the global maritime safety industry willgrow from US$16.71 billion in 2016 to US$23.67 billion in 2021 through factors such as compliancewith regulatory standards and guidelines, increased maritime awareness, and an increasing numberof incidents of piracy and terrorism.” (Research and Markets: 2016). This paper aims to analyzethe role of The International Convention for the Safety of Life at Sea (SOLAS 1974) on maritimesafety in Indonesia. And also about Who are the Main Stakeholders of Maritime Safety in Indonesia.This paper aims to increase knowledge about the 1974 Solas convention on developing maritimesafety in Indonesia. This paper aims to analyze the role of The International Convention for theSafety of Life at Sea (SOLAS 1974) on maritime safety in Indonesia. And also about Who are theMain Stakeholders of Maritime Safety in Indonesia. This paper aims to increase knowledge aboutthe 1974 Solas convention on developing maritime safety in Indonesia